For from design and through design and for design are all things - Sequeira, M. (Revista Lusófona de Arquitectura e Educação, 2014)
Academic research in architecture has mainly become a theoretical activity driven away from its subject’s core, focusing in complementary fields. Analytical investigations are common – concerning historical character, theoretical, constructive or technological – as well as propositional thesis – mainly regarding construction and technology. Yet, you can find much investigation in this scientific area, which find its significance in other domains. However, project-based theses in architecture, in which there are no antagonism or exclusion between theory and practice but rather promote complementarity, are quite scarce. This paper aims to answer the question that seems natural and consistent with the above scenario: how can we define a new paradigm, in which architecture would be understood and portrayed as a system for producing and spreading knowledge?